1993
DOI: 10.1148/radiology.189.2.8210373
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic correlates of abnormal water diffusion in cerebral ischemia: diffusion-weighted MR imaging and light and electron microscopic study.

Abstract: Diffusion-weighted images may help ascertain the extent of cellular damage and death after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 0 publications
12
104
0
Order By: Relevance
“…4). This result is consistent withˆndings in animal studies that suggested water accumulation mainly in the intracellular space in ischemic edema, even when accompanied by hyperintensity on T2-weighted image, at 6 hours 11 and cytotoxicity of edema one through 2 days 43 after onset of ischemia. Thus, the mechanism underlying decreases in FA, R2, and <ADC> during Phase 2 may be accumulation of water in the vacuoles rather than in the extracellular space.…”
Section: Magnetic Resonance In Medical Sciencessupporting
confidence: 92%
See 2 more Smart Citations
“…4). This result is consistent withˆndings in animal studies that suggested water accumulation mainly in the intracellular space in ischemic edema, even when accompanied by hyperintensity on T2-weighted image, at 6 hours 11 and cytotoxicity of edema one through 2 days 43 after onset of ischemia. Thus, the mechanism underlying decreases in FA, R2, and <ADC> during Phase 2 may be accumulation of water in the vacuoles rather than in the extracellular space.…”
Section: Magnetic Resonance In Medical Sciencessupporting
confidence: 92%
“…Although the decrease is generally attributed to cellular edema and the increase to vasogenic edema and degradation of membrane structure, 1,[10][11][12] the exact mechanisms of these changes in <ADC> remain unclear.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion tensor imaging is a new MRI modality based on the measurements of the random motion of water molecules (Basser and Jones, 2002;Basser and Pierpaoli, 1996;Le Bihan, 1995;Le Bihan et al, 2001;Le Bihan and van Zijl, 2002;Pierpaoli et al, 1993Pierpaoli et al, , 1996. Water molecules interact with many tissue components such as cell membranes, myelin, and macromolecules, which provides unique clues to the tissue architecture at the microscopic level.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, if mild vasogenic edema evolves with a dosedependent injury in the 56 Fe-irradiated brain, extravagated fluid could shift to the cytoplasm of the reactive astrocytes without significant enlargement of the extracellular space (32). The increase of net water content may be responsible for T2 prolongation in animals exposed to high doses of 56 Fe particles.…”
Section: Discussionmentioning
confidence: 99%